12x/15x

Simple and best practice solution for 12x/15x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x/15x equation:


x in (-oo:+oo)

((12*x)/15)*x = 0

4/5*x^2 = 0 // : 4/5

x^2 = 0

x = 0

x = 0

See similar equations:

| -(6-3*6)-5=-2*6-2*6+1solve | | X^7=x^4+65 | | .2(4z-10)=.8z-2 | | 1/5(4z-10=4/5z-2 | | (2-v)(2v-3)=0 | | -4(x-4)+5=6(x+4)+1 | | 2x+2X+x=940 | | 5(-6x+9)+7= | | 20x+10=60w | | 10x=5(6x-2) | | -6(5x+7)+9= | | 7(4x+3)=.5(8x+5) | | 4x=2(8+30) | | 5x=2(4x-2) | | 81x^3-w^4x^3= | | 6x-4(8-x)=17 | | 5-x=-6x | | x^2-3y=17 | | 3(6x+2)=.5(4x+4) | | 4(3x-3)=3(4x-4) | | 3z+2(4x-2)=5(3-2) | | (8x^2-4x+14)+(-7x^2+3x-10)= | | 6x=2(4x+5) | | 3(4x+-5)=9 | | 3(4+-5)=9 | | 7c+-15=-2(6(c+-3)+-4(2+-1c)) | | 6x-3(2x-1)=6(-2+1)-3x | | 2x=180-7x | | 45=k(9)(5) | | -9p=-2 | | 4.9=7.3-0.6x | | a^2bc+ab^2c+abc^2=0 |

Equations solver categories